2014
DOI: 10.1682/jrrd.2014.01.0022
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of males with transtibial amputation carrying military loads

Abstract: Abstract-The biomechanical responses to load carriage, a common task for dismounted troops, have been well studied in nondisabled individuals. However, with recent shifts in the rehabilitation and retention process of injured servicemembers, there remains a substantial need for understanding these responses in persons with lower-limb amputations. Temporalspatial and kinematic gait parameters were analyzed among 10 male servicemembers with unilateral transtibial amputation (TTA) and 10 uninjured male controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In this study, changes in MaxLat were only observed when walking up a ramp. Consistent with previous research on able-bodied participants (Birrell and Haslam, 2009;Castro et al, 2013;Harman et al, 2000;Simpson et al, 2012) and individuals with transtibial amputations (Doyle et al, 2014;Schnall et al, 2014), double support time increased when walking with a backpack. Participants in this study also walked slower when carrying a backpack, which typically increases double support time (Kirtley et al, 1985).…”
Section: Backpack Comparisonssupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, changes in MaxLat were only observed when walking up a ramp. Consistent with previous research on able-bodied participants (Birrell and Haslam, 2009;Castro et al, 2013;Harman et al, 2000;Simpson et al, 2012) and individuals with transtibial amputations (Doyle et al, 2014;Schnall et al, 2014), double support time increased when walking with a backpack. Participants in this study also walked slower when carrying a backpack, which typically increases double support time (Kirtley et al, 1985).…”
Section: Backpack Comparisonssupporting
confidence: 89%
“…A common characteristic observed when walking with a backpack load is increased forward trunk lean (Attwells et al, 2006;Caron et al, 2013;Doyle et al, 2014;Polcyn et al, 2002;Schnall et al, 2014). A recent study examined the angle between the center of mass and the ankle and knee (referenced to vertical) and demonstrated that these angles did not change with increasing load (Caron et al, 2013).…”
Section: Backpack Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schnall et al [ 5 ] found that compared to able-bodied individuals, lower-limb prosthesis users exhibit greater metabolic costs while walking with added loads, both at mid-range and high-end speeds of military foot marches. Other studies have shown that during weighted walking, lower-limb prosthesis users exhibit greater (and asymmetrical) demands on the musculoskeletal system [ 6 ] and larger deflections of the prosthetic ankle-foot system compared to unweighted walking [ 7 , 8 ]. The latter, in particular, suggests additional work focused specifically on the functional implications of these load responses is warranted.…”
Section: Introductionmentioning
confidence: 99%